Comparison between LigaSure™ and Harmonic® in Laparoscopic Sleeve Gastrectomy: A Single-Center Experience on 422 Patients. (3rd January 2019) - Velotti, N.; Manigrasso, M.; Di Lauro, K.; Vitiello, A.; Berardi, G.; Manzolillo, D.; Anoldo, P.; Bocchetti, A.; Milone, F.; Milone, M.; De Palma, G. D.; Musella, M.
Abstract : Background . New laparoscopic devices, such as electrothermal bipolar-activated devices (LigaSure™ (LS)) or ultrasonic systems (Harmonic® scalpel (HS)), have been applied recently to bariatric surgery allowing to reduce blood loss and surgical risks. The aim of this study was to retrospectively compare intraoperative performance of HS and LS, postoperative results, and clinical outcomes in a large cohort of patients undergoing LSG. Methods . Data from 422 morbidly obese patients undergoing LSG in our Bariatric Unit at the Advanced Biomedical Sciences Department of the "Federico II" University of Naples (Italy) between January 2009 and December 2017 were retrospectively analyzed. Subjects were divided into two groups (HS and LS), and operative time, intraoperative complications, and postoperative (within 30 days from surgery) complications were compared. Bleeding from the omentum or from the staple line, use of hemostatic clips, and absorbable hemostat were recorded as intraoperative complications; hemorrhages, abscess formation, gastric leaks, fever, and mortality were considered as postoperative complications. Results . Statistical analysis showed no difference in terms of baseline demographics between the two cohorts. Operative time (48 ± 9 vs 49 ± 6 min, p = 0.646 ) and the rates of intraoperative and postoperative complications did not significantly differ between groups. Conclusion . Harmonic® and LigaSure™ are both useful tools in bariatric surgery, and these two advanced power devices are user-friendly and can facilitate surgeon work; from this point of view, the choice of the energy device should be based on the preference of the surgeon and on the hospital costs policy and availability.